The development and evaluation of an ultrasonic fatigue unit - Clifton, T. E. (College of Aeronautics, 1963)
A fatigue test apparatus operating at 20 kc/s is described. The unit is based on a standard magnetostrictive drive system as used in high energy stresswave generators. An automatic counting device has been developed and incorporated in the final equipment, resulting in improvements in accuracy and reproducibility of results. Some typical results of tests on aluminium alloys are presented.